Kehormatan dari Shogun pada Seppuku dalam Kisah 47 Ronin - Hariandja, Grace Junita Tiarida (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 6 No 2 (2024), 2024)
The study aims to describe the reasons for seppuku as an honor given to the ronin in the story of the 47 Ronin. This research uses descriptive methods and a qualitative approach and uses reading and writing techniques to process data collected from excerpts from the story 47 Ronin written by John Allyn. Based on data findings, the seppuku carried out in this story was an honor given by the Shogun to the samurai because of their loyalty to their dead master even though the ronin had violated many existing rules. The Shogun granted this right because he felt that this was something that fulfilled his sense of justice. After seeing the struggle put up by the ronin and how sincerely they served their master, this moved the Shogun to give the ronin a respectful punishment. Also in the case of Lord Asano, the Shogun gave him the honor of seppuku considering Lord Asano's high rank and long service that had been passed down from his ancestors. This is all written in the story of the 47 Ronin explicitly and the author will discuss it in this research.